Early calf segregation enables development of bovine tuberculosis-free replacement stock in a highly infected dairy herd: a preliminary study in Ethiopia - Lakew, Matios; Tadesse, Biniam; Bedada, Wegene; Wakjira, Bayeta Senbata; Mekonnen, Getnet Abie; Chibssa, Tesfaye Rufael; Ashenafi, Hagos; Ameni, Gobena; Conlan, Andrew J. K.; Bakker, Douwe; Gumi, Balako; Kapur, Vivek (Frontiers in Veterinary Science, 2025)
Bovine tuberculosis (bTB) severely impacts Ethiopia’s growing dairy sector, where test-and-cull control methods are economically unfeasible, and test-and-segregation is impractical in herds with very high prevalence. We assessed the feasibility of establishing bTB-free replacement stock through early segregation of calves born to bTB-positive cows. In a two-year longitudinal study on a high-prevalence (98% tuberculin skin test positive) dairy farm, 26 newborn calves were separated from their bTB-positive dams on day five after birth and screened for bTB at 2 to 5 month intervals across eight rounds, with test-positive calves immediately removed from the negative herd. The majority of segregated calves (19 out of 25; 76%; 95% CI: 58–94) remained bTB-test negative through the testing period, with nine uninfected female calves and two males reaching 18 months of age, demonstrating potential for establishing bTB-free breeding stock. However, six calves (24%; 95% CI: 6–42) turned to test positive during the study period. The extended dam-calf contact during the first five days likely contributed to some infections, suggesting that immediate separation and alternative colostrum sources could improve success rates. The addition of interferon gamma release assays in later testing rounds enabled detection of infected animals potentially missed by skin testing alone, highlighting the value of complementary diagnostic approaches for surveillance. These findings provide preliminary evidence that early calf segregation can generate bTB-negative replacement stock from infected herds, and provide a framework for larger-scale studies across different farm settings.